The osmorespiratory compromise: Physiological responses and tolerance to hypoxia are affected by salinity acclimation in the euryhaline Atlantic killifish (Fundulus heteroclitus) - Giacomin, Marina Mussoi; Bryant, Heather J.; Val, Adalberto Luis; Schulte, Patricia; Wood, Chris M. (Journal of Experimental Biology, 2019)
The characteristics of the fish gill that maximize gas exchange are the same that promote diffusion of ions and water to and from the environment; therefore, physiological trade-offs are likely to occur.Here, we investigated how salinity acclimation affects whole-animal respiratory gas exchange during hypoxia using Fundulus heteroclitus, a fish that inhabits salt marshes where salinity and oxygen levels vary greatly. Salinity had marked effects on hypoxia tolerance, with fish acclimated to 11 and 35 ppt showing much longer time to loss of equilibrium(LOE) in hypoxia than 0 ppt-acclimated fish. Fish acclimated to 11 ppt (isosmotic salinity) exhibited the greatest capacity to regulate oxygen consumption rate (MO2) under hypoxia, as measured through the regulation index (RI) and Pcrit. At 35 ppt, fish had a higher routine metabolic rate (RMR) but a lower RI than fish at 11 ppt, but there were no differences in gill morphology, ventilation or blood O2 transport properties between these groups. In contrast, 0 ppt-acclimated fish had the highest ventilation and lowest O2 extraction efficiency in normoxia and hypoxia, indicating a higher ventilatory workload in order to maintain similar levels of MO2. These differences were related to alterations in gill morphology, where 0 ppt-acclimated fish had the smallest lamellar surface area with the greatest epithelial cell coverage (i.e. thicker lamellae, longer diffusion distance) and a larger interlamellar cell mass, contrasting with 11 ppt-acclimated fish, which had overall the highest respiratory surface area. The alteration of an array of physiological parameters provides evidence for a compromise between salinity and hypoxia tolerance in killifish acclimated to freshwater. © 2019. Published by The Company of Biologists Ltd | Journal of Experimental Biology.